Acute effects on glucose tolerance by neprilysin inhibition in patients with type 2 diabetes. Issue 10 (21st July 2022) - Wewer Albrechtsen, Nicolai J.; Møller, Andreas; Martinussen, Christoffer; Gluud, Lise L.; Rashu, Elias B.; Richter, Michael M.; Plomgaard, Peter; Goetze, Jens P.; Kjeldsen, Sasha; Hansen, Lasse Holst; Gustafsson, Finn; Deacon, Carolyn F.; et al.
Abstract: Aims: Sacubitril/valsartan is a neprilysin‐inhibitor/angiotensin II receptor blocker used for the treatment of heart failure. Recently, a post‐hoc analysis of a 3‐year randomized controlled trial showed improved glycaemic control with sacubitril/valsartan in patients with heart failure and type 2 diabetes. We previously reported that sacubitril/valsartan combined with a dipeptidyl peptidase‐4 inhibitor increases active glucagon‐like peptide‐1 (GLP‐1) in healthy individuals. We now hypothesized that administration of sacubitril/valsartan with or without a dipeptidyl peptidase‐4 inhibitor would lower postprandial glucose concentrations (primary outcome) in patients with type 2 diabetes via increased active GLP‐1. Methods: We performed a crossover trial in 12 patients with obesity and type 2 diabetes. A mixed meal was ingested following five respective interventions: (a) a single dose of sacubitril/valsartan; (b) sitagliptin; (c) sacubitril/valsartan + sitagliptin; (d) control (no treatment); and (e) valsartan alone. Glucose, gut and pancreatic hormone responses were measured. Results: Postprandial plasma glucose increased by 57% (incremental area under the curve 0‐240 min) ( p  = .0003) and increased peak plasma glucose by 1.7 mM (95% CI: 0.6‐2.9) ( p  = .003) after sacubitril/valsartan compared with control, whereas postprandial glucose levels did not change significantly after sacubitril/valsartan + sitagliptin. Glucagon, GLP‐1 and C‐peptide concentrations increased after sacubitril/valsartan, but insulin and glucose‐dependent insulinotropic polypeptide did not change. Conclusions: The glucose‐lowering effects of long‐term sacubitril/valsartan treatment reported in patients with heart failure and type 2 diabetes may not depend on changes in entero‐pancreatic hormones. Neprilysin inhibition results in hyperglucagonaemia and this may explain the worsen glucose tolerance observed in this study. ClinicalTrials.gov (NCT03893526).